Dinamika Ekonomi Digital dan Implikasinya terhadap Model Bisnis - Maya Listanti; Fery Angga Saputra; Anjumi Zia Ulhaq (Cyber Media Indonesia, 2025)
The development of the digital economy has fundamentally transformed market structures, consumer behavior, and organizational operations. This article aims to analyze the dynamics of the digital economy and its implications for business model transformation through a literature review approach. The study examines various scholarly works related to digitalization, technological innovation, platform economy, big data, and shifts in value propositions within modern organizations. The findings indicate that the digital economy accelerates the transition from conventional business models toward platform-based, ecosystem-oriented, and data-driven strategies. Digital transformation enhances operational efficiency, expands market reach, and enables service personalization through data analytics. Nevertheless, challenges such as industry disruption, cybersecurity risks, and digital inequality remain critical strategic concerns that require adaptive management. Therefore, firms must develop dynamic capabilities, continuous innovation, and integrated digital transformation strategies to sustain competitiveness. This article provides a conceptual contribution to understanding the relationship between digital economic dynamics and the evolution of business models in contemporary management discourse. Abstrak Perkembangan ekonomi digital telah mengubah secara fundamental struktur pasar, perilaku konsumen, serta pola operasional perusahaan. Artikel ini bertujuan untuk menganalisis dinamika ekonomi digital dan implikasinya terhadap transformasi model bisnis melalui pendekatan kajian pustaka. Studi ini menelaah berbagai literatur terkait digitalisasi, inovasi teknologi, platform economy, big data, serta perubahan value proposition dalam organisasi modern. Hasil kajian menunjukkan bahwa ekonomi digital mendorong pergeseran dari model bisnis konvensional menuju model berbasis platform, ekosistem, dan data-driven strategy. Digitalisasi juga meningkatkan efisiensi operasional, memperluas akses pasar, serta memungkinkan personalisasi layanan berbasis analitik data. Namun demikian, tantangan seperti disrupsi industri, keamanan siber, dan ketimpangan digital tetap menjadi isu strategis yang harus dikelola secara adaptif. Oleh karena itu, perusahaan dituntut untuk mengembangkan kapabilitas dinamis, inovasi berkelanjutan, dan strategi transformasi digital yang terintegrasi. Artikel ini memberikan kontribusi konseptual dalam memahami hubungan antara dinamika ekonomi digital dan evolusi model bisnis dalam konteks manajemen kontemporer.